PEDOT-Based Conducting Polymer Actuators - Hu, Faqi; Xue, Yu; Xu, Jingkun; Lu, Baoyang (Frontiers in Robotics and AI, 2019)
Conducting polymers, particularly poly(3,4-ethylenedioxythiophene) (PEDOT) and its complex with poly(styrene sulfonate) (PEDOT:PSS), provide a promising materials platform to develop soft actuators or artificial muscles. To date, PEDOT-based actuators are available in the field of bionics, biomedicine, smart textiles, microactuators, and other functional applications. Compared to other conducting polymers, PEDOT provides higher conductivity and chemical stability, lower density and operating voltages, and the dispersion of PEDOT with PSS further enriches performances in solubility, hydrophility, processability, and flexibility, making them advantageous in actuator-based applications. However, the actuators fabricated by PEDOT-based materials are still in their infancy, with many unknowns and challenges that require more comprehensive understanding for their current and future development. This review is aimed at providing a comprehensive understanding of the actuation mechanisms, performance evaluation criteria, processing technologies and configurations, and the most recent progress of materials development and applications. Lastly, we also elaborate on future opportunities for improving and exploiting PEDOT-based actuators.